(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article talks about the re-inventory of the existing network of routes in the city of Asaka, Andijan region, the reconsideration of the network of overlapping routes, and optimization measures in each section of the route.